Effects of p-Aminosalicylic acid on the Neurotoxicity of Manganese and Levels of Dopamine and Serotonin in the Nervous System and Innervated Organs of Crassostrea virginica - King, Candice (2008)
Manganese is a neurotoxin causing Manganism in individuals chronically exposed to elevated levels in their environment. Toxic manganese exposure causes mental and emotional disturbances, and a movement disorder similar to Idiopathic Parkinsons Disease. Manganese interferes with dopamine neurons involved in control of body movements. Recently, p-aminosalicylic acid (PAS) is being used to alleviate symptoms of Manganism, but its mechanism of action is unknown. The eastern oyster, Crassostrea virginica, possesses a dopaminergic innervation of its gill. Oysters exposed to manganese have reduced levels of dopamine in the cerebral ganglia, visceral ganglia and gill, but not of norepinephrine, octopamine or serotonin. Those results are consistent with reported mechanisms of action of manganese in human and mammalian systems. In this study we determined the effects of PAS treatments on dopamine and serotonin levels in oysters exposed to manganese. Adult C. virginica were exposed to 500 µM and 1 mM of manganese with and without 500 µM and 1 mM of PAS by removing one shell and maintaining the animals in individual containers of aerated artificial sea water at 18° C for 3 days. Control animals were similarly treated without manganese or PAS. Dopamine and serotonin levels were measured by HPLC with fluorescence detection. PAS protected the ganglia and gill against the effects of 500 µM manganese, but not against the 1 mM manganese treatments. Serotonin levels were not affected by the treatments. The study demonstrates PAS can protect against reductions in dopamine levels caused by neurotoxic manganese exposure, but is concentration dependent. These findings may provide insights into the actions of PAS in therapeutic treatments of Manganism.